The influence of heat treatment on discharge and electrochemical properties of Mg-Gd-Zn magnesium anode with long period stacking ordered structure for Mg-air battery. (20th January 2021) - Chen, Xingrui; Wang, Henan; Zou, Qi; Le, Qichi; Wen, Cuie; Atrens, Andrej
Abstract: This work investigates the influence of heat treatment on the discharge and electrochemical properties of Mg95.28 Gd3.72 Zn1.00 alloy as an anode for the Mg-air battery. The heat treatment removes the (Mg, Zn)3 Gd eutectic phase and produces the long period stacking ordered (LPSO) structure. The T6 heat treated Mg95.28 Gd3.72 Zn1.00 alloy shows good discharge performance, including the high and stable cell voltage, high discharge capacity and anodic efficiency, and good specific energy output. The T6 treated Mg95.28 Gd3.72 Zn1.00 anode has (i) the best discharge capacity and anodic efficiency of 1329 mAh g −1 and 59.9%, respectively, at 40 mA cm −2, which is 21.4% and 23.3% higher than the as-cast anode, and (ii) the highest specific energy of 1504 mW h g −1, which is 46.4% higher than the as-cast anode. These improved discharge properties are attributed to the LPSO structure, which provides moderate and even stimulation for the dissolution of the α-Mg and helps to exfoliate the discharge products. In contrast, the (Mg, Zn)3 Gd phase produces a passive film, leading to the voltage drop.